Analysis Of Welfare Level Of Singkong Farmers In Sukadana Ilir Village, East Lampung - Suripto Suripto; Intan Kumala Sari; Istanti Istanti (Universitas 17 Agustus 1945 Semarang, 2023)
This study aims to analyze the level of welfare of cassava farmers in Sukadana Ilir Village, Sukadana District, East Lampung Regency. This research was conducted specifically in Sukadana Ilir Village using 80 samples of respondents who work as cassava farmers. The analytical method used is chi-square. The results based on the chi-square results, there is an effect for the variables of land area and income on the welfare of cassava farmers in Sukadana Ilir Village and there is no effect for the education level variable on the welfare of cassava farmers in Sukadana Ilir Village. The level of welfare in Sukadana Ilir Village is in the high category, namely KS3.